2020
DOI: 10.3390/ijerph17020390
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to Increasing Adolescent Physical Activity and Wellbeing: A Mediation Analysis of Intervention Components Designed Using a Participatory Approach

Abstract: We assessed which intervention components were associated with change in moderate-to-vigorous physical activity (MVPA) and wellbeing through proposed psychosocial mediators. Eight schools (n = 1319; 13–14 years) ran GoActive, where older mentors and in-class-peer-leaders encouraged classes to conduct two new activities/week; students gained points and rewards for activity. We assessed exposures: participant-perceived engagement with components (post-intervention): older mentorship, peer leadership, class sessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 75 publications
2
11
0
1
Order By: Relevance
“…Moreover, despite the behaviour change resources and delivery strategy being developed using participatory approaches [ 31 ], the implementation evaluation suggested that the delivered intervention may not have met the needs or expectations of the adolescents as engagement with the Facebook group and materials declined over time [ 43 ]. This is consistent with a recent study that showed no effects on adolescents’ physical activity despite considerable input from the target group [ 66 ]. There is a need for further research to establish the impact of wearable activity trackers, either alone or in combination with additional strategies, on adolescents’ physical activity levels, and examine what factors may be critical for changing behaviour.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, despite the behaviour change resources and delivery strategy being developed using participatory approaches [ 31 ], the implementation evaluation suggested that the delivered intervention may not have met the needs or expectations of the adolescents as engagement with the Facebook group and materials declined over time [ 43 ]. This is consistent with a recent study that showed no effects on adolescents’ physical activity despite considerable input from the target group [ 66 ]. There is a need for further research to establish the impact of wearable activity trackers, either alone or in combination with additional strategies, on adolescents’ physical activity levels, and examine what factors may be critical for changing behaviour.…”
Section: Discussionsupporting
confidence: 93%
“…Likewise, Gonzalo-Silvestre’s study [ 45 ] also showed self-concept as a good predictor of quality of life. Therefore, the present research aims to contribute to the improvement in mental well-being in children and adolescents through the proposal of a theoretical model based on the importance of physical activity as a predictor of health-related quality of life [ 49 ] through constructs that affect the development of the psychological well-being of adolescents [ 50 ], such as subjective happiness and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Chapter Introduction and background T his report includes text from the authors' published articles. [1][2][3][4][5][6] All of these articles are Open Access articles distributed in accordance with the terms of the Creative Commons Attribution (CC BY 4.0) license, which permits others to distribute, remix, adapt and build upon this work, for commercial use, provided the original work is properly cited. See: http://creativecommons.org/licenses/by/4.0/.…”
Section: Resultsmentioning
confidence: 99%
“…This is supported by mediation analyses that suggest that, even though no evidence was found to support the use of GoActive intervention components in increasing physical activity, higher perceived mentor and teacher support was associated with improved well-being among boys and girls via various mediators, including self-efficacy, self-esteem and social support. 2 The context of an intervention cannot be overlooked or undervalued. Although the intervention itself was complex in nature, its interaction with its context was also highly complex.…”
Section: Methodsmentioning
confidence: 99%